Verification of the accuracy and reliability of the TrackMan tennis radar - Murata, M.; Takahashi, H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
TrackMan, a device used to measure the kinematics of a ball in flight, has recently been used for research and coaching purposes in tennis, and the number of studies on this device is expected to increase. This study is focused on verifying the accuracy of TrackMan; three participants performed services with various velocities and angular velocity combinations. TrackMan and a proven method based on computer vision were used to measure the speed, spin rate, and spin axis of the ball. The results obtained using each method were compared using regression analysis, intraclass correlation coefficients, and Bland-Altman analysis. The speed and spin rate of the two methods agreed well; the degree of error would not be problematic in practical applications. However, TrackMan underestimated the speed if it was unable to detect the hitting position. The spin axis measured by TrackMan was unstable under low spin rate conditions (<3000 rpm). Furthermore, the standard deviation of the spin axis measurement error exceeded the difference between the average slice and kick service spin axes reported in the previous study, so the spin axis measurement accuracy was very low for research purposes, even when the spin rate was above 3000 rpm. For those who are aware of the existence of outliers, TrackMan can be useful for coaching because it provides instant feedback. Similarly, the measured rotational speed and spin rate could be used in the study.